SCHOLARSHIP OF TEACHING AND LEARNING DALAM PENDIDIKAN TINGGI KRISTEN DI INDONESIA: MENUJU PENDEKATAN PEDAGOGI BERBASIS IMAN [SCHOLARSHIP OF TEACHING AND LEARNING IN CHRISTIAN HIGHER EDUCATION IN INDONESIA: TOWARDS A FAITH BASED PEDAGOGICAL APPROACH] - Lo, Sarinah (Polyglot, 2025)
This article critically examines the shifting focus among higher education faculty in Indonesia—particularly within Christian institutions—from teaching to research, driven by academic policies that prioritize scholarly publication. Using a literature-based approach and the framework of the Scholarship of Teaching and Learning (SoTL), the paper explores global developments, conceptual challenges, and the relevance of SoTL for faith-integrated learning. While SoTL practices in Indonesia and Christian institutions remain limited, the study highlights their strategic potential to strengthen reflective, collaborative, and transformative pedagogy. The article concludes with recommendations for building a faith-informed SoTL ecosystem within the context of Christian higher education in Indonesia. Abstrak Bahasa Indonesia Tulisan ini mengkaji pergeseran fokus dosen pendidikan tinggi di Indonesia—khususnya di institusi Kristen—dari pengajaran ke penelitian akibat kebijakan akademik yang menekankan publikasi ilmiah. Dengan pendekatan studi pustaka dan kerangka Scholarship of Teaching and Learning (SoTL), artikel ini menelusuri perkembangan global, tantangan konseptual, serta relevansi SoTL bagi integrasi iman dan pembelajaran. Kajian ini menunjukkan bahwa meskipun praktik SoTL di Indonesia dan institusi Kristen masih terbatas, pendekatan ini memiliki potensi strategis untuk memperkuat pedagogi reflektif, kolaboratif, dan transformatif. Artikel ini juga menawarkan rekomendasi untuk membangun ekosistem SoTL berbasis iman dalam konteks pendidikan tinggi Kristen di Indonesia.